2015
DOI: 10.1093/cid/civ981
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness and Budget Impact of 2-Drug Dolutegravir-Lamivudine Regimens for the Treatment of HIV Infection in the United States

Abstract: Should DTG + 3TC demonstrate high rates of virologic suppression, this regimen will be cost-effective and would save >$500 million in ART costs in the United States over 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…Such a treatment regimen could be an interesting alternative to classical triple-ART in selected patients. Furthermore, dual therapy might be a cost-effective global ART strategy 38 . A number of large prospective studies evaluating the efficacy of DTG-based dual therapy are under way and will inform its potential implementation at a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…Such a treatment regimen could be an interesting alternative to classical triple-ART in selected patients. Furthermore, dual therapy might be a cost-effective global ART strategy 38 . A number of large prospective studies evaluating the efficacy of DTG-based dual therapy are under way and will inform its potential implementation at a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy may offer cost or toxicity advantages over the current 3-drug regimens. 56 To date, only 2 adequately powered randomized clinical trials have demonstrated noninferior outcomes of 2-drug therapy compared with 3-drug regimens. Lopinavir/r plus lamivudine was noninferior to lopinavir/r plus 2 NRTIs in one study, 57 and darunavir/r plus raltegravir was noninferior to darunavir/r plus 2 NRTIs in another.…”
Section: Recommended Initial Regimensmentioning
confidence: 99%
“…Several studies have proven the non‐inferiority or superiority of DTG, with its more tolerable side effect profile, high genetic barrier to resistance, and decreased time to virologic suppression, compared to alternative first‐line antiretroviral agents (Table , Appendix ) . In addition to DTG's excellent clinical profile, it has also been shown to be an economically attractive strategy in both treatment‐naïve and treatment‐experienced patients in North America and Europe .…”
Section: Introductionmentioning
confidence: 99%